2021
DOI: 10.1017/dem.2020.34
|View full text |Cite
|
Sign up to set email alerts
|

Can the historical gender gap index deepen our understanding of economic development?

Abstract: Knowledge of the long relationship between gender equality and economic growth is hampered by the lack of information and resources on the various dimensions of gender equality. This paper is a first attempt to assess the size of the gender gap and investigate its relationship with economic growth from a historical perspective. Exploiting a unique census-based dataset of 86 French counties in the mid-nineteenth century, I construct a historical gender gap index measuring the size of the gap between men and wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 51 publications
(66 reference statements)
3
8
0
Order By: Relevance
“…Several studies have explored the relationship between gender inequality in education and economic growth. And earlier research has shown a positive link between the gender gap in education and economic growth ( Barro and Sala-i-martin 1995 ; Seguino, 2000 ; Baliamoune-Lutz and McGillivray, 2009 ; Elson, 2009 ; Klasen and Lamanna, 2009 ), and recent analyses reveal the adverse effects of gender disparities in education on economic growth, using newer data and more careful econometric techniques ( Karoui and Feki, 2018 ; Minasyan et al, 2019 ; Braunstein et al, 2020 ; McGee et al, 2020 ; Perrin, 2021 ; Santos Silva and Klasen, 2021 ; Girón and Kazemikhasragh, 2022 ). Notably, countries with the largest gender gaps lead to greater economic losses.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several studies have explored the relationship between gender inequality in education and economic growth. And earlier research has shown a positive link between the gender gap in education and economic growth ( Barro and Sala-i-martin 1995 ; Seguino, 2000 ; Baliamoune-Lutz and McGillivray, 2009 ; Elson, 2009 ; Klasen and Lamanna, 2009 ), and recent analyses reveal the adverse effects of gender disparities in education on economic growth, using newer data and more careful econometric techniques ( Karoui and Feki, 2018 ; Minasyan et al, 2019 ; Braunstein et al, 2020 ; McGee et al, 2020 ; Perrin, 2021 ; Santos Silva and Klasen, 2021 ; Girón and Kazemikhasragh, 2022 ). Notably, countries with the largest gender gaps lead to greater economic losses.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Interestingly, our results confirm the importance of the industrialization process, the demographic transition, and cultural attitudes with regard to the family sphere (captured by the marriage pattern) as incremental factors for economic growth. Beyond the importance of the role played by greater gender equality, our findings show that counties that economically performed better, in other words, that displayed a higher level of GDP per capita, were characterized by wider industrial employment, lower fertility and mortality rates, 34 a higher share of married women and women who married at a younger age (falling in line with the pattern found by Perrin (2022a, 2022b) for France), as well as lower emigration and higher immigration.…”
Section: Gender Outcomes and Implications For Economic Developmentsupporting
confidence: 84%
“…Perrin (2021) provides empirical evidence of the association of gender equality and family systems with economic development, and confirms the relevance of the association as identified by exploratory methods.…”
supporting
confidence: 67%